Differentially expressed lnc‐NOS2P3‐miR‐939‐5p axis in chronic heart failure inhibits myocardial and endothelial cells apoptosis via iNOS/TNFα pathway. Issue 19 (25th August 2020) - Chen, Cuncun; Zong, Ming; Lu, Ying; Guo, Yide; Lv, Honggen; Xie, Lihong; Fu, Zhiyan; Cheng, Yu; Si, Yuying; Ye, Bei; Fan, Lieying
Abstract: Inflammatory cytokine‐induced cell apoptosis is important for initiation and progression of chronic heart failure (CHF). Non‐coding RNAs, including long non‐coding RNAs and microRNAs, have emerged as critical regulators of this pathological process. The role in regulating inflammation and induction to cell apoptosis in CHF is not well understood. This study found CHF patients had elevated serum miR‐939‐5p, with greater increase in New York Heart Association (NYHA) I‐II patients than in NYHA III‐IV. Moreover, miR‐939‐5p was positively correlated with B‐type natriuretic peptide (BNP) in NYHA III‐IV patients, while not in NYHA I‐II. Further study showed miR‐939‐5p mimics promoted cell proliferation and inhibited inflammatory cytokine‐induced apoptosis of HUVECs and H9C2, while inhibition of endogenous miR‐939‐5p produced the opposite effects. Induced nitric oxide synthase (iNOS) and tumour necrosis factor α (TNFα) were identified as target genes of miR‐939‐5p. Additionally, lncRNA‐NOS2P3 acted as an endogenous sponge RNA to inhibit miR‐939‐5p expression, regulate the expression of iNOS/TNFα and control inflammation‐induced cells apoptosis. These suggest that CHF patients exhibited elevated serum miR‐939‐5p level especially in NYHA I‐II grades. And lnc‐NOS2P3‐miR‐939‐5p‐iNOS/TNFα pathway regulated inflammatory cytokine‐induced endothelial and myocardial cells apoptosis and provided a promising strategy for diagnosis and treatment of CHF.